Analisis Pengaruh Kualitas Layanan Website DRPD Jawa Timur Terhadap Kepuasan Pengguna dengan Metode Webqual 4.0 Modifikasi - Mochamad Winnedi Fitrayana; Bambang Hariadi; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
As the elements of regional goverments East Java DPRD  has an important role in order to improve the citizents welfare, therefore it is expected DPRD activities can be widely known by the people of Jawa Timur. The official website of East Java DPRD, named www.dprd.jatimprov.go.id provide information about council’s activity agenda,council organization structure, digital library, task and responsibilities and parliament news is expected to provide an overview about DPRD activities.According to the interview with the staff of East Java DPRD, there is a broken link in the current website. DPRD Jawa Timur currently planned to improve the current website, therefore DPRD requires feedback for the evalution. The solution give is by conducting a study about analysis of the influence of website quality towards user satisfaction. The analysis is based on Webqual 4.0, according to (Barnes & Vidgen, 2003) Webqual 4.0 is one of the methods of measuring website quality based on user perceptions. WebQual 4.0 consist of 3 categories namely Information Quality, Service Quality and Usability, but in this study added 4th category called User Interface Quality(Hasan, 2014). All of 4 variables will be used as a reference to construct the questionnaire, the results of this research Information Quality,Service Quality and User Interface Quality has a positive influence towards user satisfaction. Further recommendations are given in the form of  Graphical User Interface (GUI) design to improve the website.